Molecular Imaging of Growth, Metabolism, and Antibiotic Inhibition in Bacterial Colonies by Laser Ablation Electrospray Ionization Mass Spectrometry. (4th October 2016) - Li, Hang; Balan, Pranav; Vertes, Akos
Abstract: Metabolism in microbial colonies responds to competing species, rapidly evolving genetic makeup, and sometimes dramatic environmental changes. Conventional characterization of the existing and emerging microbial strains and their interactions with antimicrobial agents, e.g., the Kirby–Bauer susceptibility test, relies on time consuming methods with limited ability to discern the molecular mechanism and the minimum inhibitory concentration. Assessing the metabolic adaptation of microbial colonies requires their non‐targeted molecular imaging in a native environment. Laser ablation electrospray ionization (LAESI) is an ambient ionization technique that in combination with mass spectrometry (MS) enables the analysis and imaging of numerous metabolites and lipids. In this contribution, we report on the application of LAESI‐MS imaging to gain deeper molecular insight into microbe–antibiotic interactions, and enhance the quantitative nature of antibiotic susceptibility testing while significantly reducing the required incubation time.